Identification of a novel RPGRIP1 mutation in an Iranian family with leber congenital amaurosis by exome sequencing. Issue 3 (29th November 2017) - Imani, Saber; Cheng, Jingliang; Mobasher‐Jannat, Abdolkarim; Wei, Chunli; Fu, Shangyi; Yang, Lisha; Jadidi, Khosrow; Khosravi, Mohammad Hossein; Mohazzab‐Torabi, Saman; Shasaltaneh, Marzieh Dehghan; Li, Yumei; Chen, Rui; et al.
Abstract: Leber congenital amaurosis (LCA) is a heterogeneous, early‐onset inherited retinal dystrophy, which is associated with severe visual impairment. We aimed to determine the disease‐causing variants in Iranian LCA and evaluate the clinical implications. Clinically, a possible LCA disease was found through diagnostic imaging, such as fundus photography, autofluorescence and optical coherence tomography. All affected patients showed typical eye symptoms associated with LCA including narrow arterioles, blindness, pigmentary changes and nystagmus. Target exome sequencing was performed to analyse the proband DNA. A homozygous novel c. 2889delT (p.P963 fs) mutation in the RPGRIP1 gene was identified, which was likely the deleterious and pathogenic mutation in the proband. Structurally, this mutation lost a retinitis pigmentosa GTPase regulator (RPGR)‐interacting domain at the C‐terminus which most likely impaired stability in the RPGRIP1 with the distribution of polarised proteins in the cilium connecting process. Sanger sequencing showed complete co‐segregation in this pedigree. This study provides compelling evidence that the c. 2889delT (p.P963 fs) mutation in the RPGRIP1 gene works as a pathogenic mutation that contributes to the progression of LCA.